(MIS3 & 2) millennial oscillations in Greenland dust and Eurasian aeolian records – A paleosol perspective. (1st August 2017) - Rousseau, Denis-Didier; Boers, Niklas; Sima, Adriana; Svensson, Anders; Bigler, Matthias; Lagroix, France; Taylor, Samuel; Antoine, Pierre
Abstract: Since their discovery, the abrupt climate changes that punctuated the last glacial period (∼110.6–14.62 ka) have attracted considerable attention. Originating in the North-Atlantic area, these abrupt changes have been recorded in ice, marine and terrestrial records all over the world, but especially in the Northern Hemisphere, with various environmental implications. Ice-core records of unprecedented temporal resolution from northern Greenland allow to specify the timing of these abrupt changes, which are associated with sudden temperature increases in Greenland over a few decades, very precisely. The continental records have, so far, been mainly interpreted in terms of temperature, precipitation or vegetation changes between the relatively warm "Greenland Interstadials" (GI) and the cooler "Greenland Stadials" (GS). Here we compare records from Greenland ice and northwestern European eolian deposits in order to establish a link between GI and the soil development in European mid-latitudes, as recorded in loess sequences. For the different types of observed paleosols, we use the correlation with the Greenland records to propose estimates of the maximum time lapses needed to achieve the different degrees of maturation and development. To identify these time lapses more precisely, we compare two independent ice-core records: δ 18 O and dust concentration, indicating variations of atmospheric temperature and dustiness in the Greenland area, respectively. Our method slightly differs from the definition of a GI event duration applied in other studies, where the sharp end of the δ 18 O decrease alone defines the end of a GI. We apply the same methodology to both records (i.e., the GIs are defined to last from the beginning of the abrupt δ 18 O increase or dust concentration decrease until the time when δ 18 O or dust recur to their initial value before the GI onset), determined both visually and algorithmically, and compare them to published estimates of GI timing and duration. The duration of the GI and consequently the maximum time for paleosol development varies between 200 and 4200 years when visually determined and between 200 and 4800 years when estimated algorithmically for GI 17 to 2, i.e. an interval running from 60 ka to 23 ka b2k (age before 2000 AD). Furthermore, we investigate the abruptness of the transition from stadial to interstadial conditions, which initiates the paleosol development. The average transition duration is 55.4 ± 16.1 (56.8 ± 19.6) years when determined visually, and 36.4 ± 13.4 (60.00 ± 21.2) years when determined algorithmically for the δ 18 O (dust concentration). The δ 18 O increases correspond to a mean temperature difference of 11.8 °C on the top of the Greenland ice sheet, associated with substantial reorganizations of the ecosystems in mid-latitude Europe. Highlights: European loess sequences record paleosols are correlated with Greenland interstadials (Dansgaard-Oeschger events). During these interstadials, dust deposition did not occur in Europe. δ 18 O and dust Greenland interstadials do not always start on the same date and their duration is between 60 and 15 ka b2k. The maturation of the paleosols corresponds to the duration of the Greenland interstadials between 4800 and 200 years. Two categories of paleosol maximum development: between 1000 and 200 years and between 1600 and 4800 years. The paleosol maturation better constraint the timing of the eolian deposition used to estimate the mass accumulation rates.